Role of Genetic Factors in the Causation of Non-Syndromic Hearing Loss (NSHL) in Indian Population - Sultana, Shehnaz; Nallari, Pratibha; Ananthapur, Venkateshwari (Archives of Clinical and Biomedical Research, 2020)
Hearing loss affects about 70 million people worldwide, which can be inherited as either syndromic or non-syndromic forms. Approximately 50% of all childhood deafness is caused due to gene defects. The Non-syndromic hearing loss (NSHL) is extremely heterogenous trait inherited as autosomal recessive, autosomal dominant and X-linked and also due to mitochondrial mutations. In the present review genes causing non-syndromic hearing loss (NSHL) are classified based on their molecular function. GJB2 is most prominent deafness causing gene among the different populations including India, followed by other genes. The recent technological advances in target-enrichment methods and next generation sequencing has overcome the barriers possessed by the earlier methods and laid the path for comprehensive analysis of all the known genes causing non-syndromic hearing loss. The review mainly emphases on the genes causing non-syndromic hearing loss in Indian population and their molecular function. Identifying the genes responsible for hearing loss enables otolaryngologists, geneticist to apply molecular diagnosis by offering genetic testing which helps in prevention of the condition of non-syndromic hearing loss, proper diagnosis, management, pre-natal diagnosis and to offer genetic counselling.